An Attempt to Assess Expansion Strategy through Acquisition based upon Bosch–Siemens and Zelmer Transaction - Wójtowicz, Adrian (Journal of Finance and Financial Law, 2014)
Mergers and acquisitions are a significant strategy of companies’ development in the present globalized economy. An expansion through acquisition has been choosen by BSH group, which took over Zelmer SA company – Central and Eastern Europe leader in production of small home appliances. BSH is a global manufacturer of home appliances. The article analyzes both companies and the reasonableness of the transaction in the context of BSH group development. The author assessed that the transaction contributed to growth of the group’s market share in Central and Eastern Europe. Furthermore, the transaction also contributed to expansion of the group’s product portfolio.